Determinants of Shari'ah governance disclosure in financial institutions: Evidence from Saudi Arabia. Issue 2 (17th December 2018) - Azid, Toseef; Alnodel, Ali A.
Abstract : Purpose: This paper aims to investigate factors influencing Shari'ah governance disclosure (SGD) in financial institutions. Design/methodology/approach: Using content analysis approach, 46 annual reports published in 2015 by banks and insurance companies were investigated based on a self-constructed disclosure index. Findings: The results show that the average level of voluntary disclosure of Shari'ah governance in Saudi financial institutions is 11.7 per cent, which is lower than expectations Moreover, regression analysis shows that industry type, ownership structure and board composition significantly determine the extent of voluntary disclosure of Shari'ah governance. Local financial institutions which are owned by non-governmental agencies are more likely to disclose voluntarily their Shari'ah governance, in particular from the banking industry. Research limitations/implications: It also bridges the gap between theory and practice and can be used to practice economic and commercial impact in teaching to influence public policy in research contributing to the body of knowledge and especially for the insurance sector and government. Social implications: It provides guidance to the ethical investors and supports them in the decision-making process. Originality/value: This research extends the investigation of SGD into insurance sector in a country that has a general policy about adhering to Islamic principles. Financial institutions might go beyond the country affirmations to legitimate their identity in response to the society critiques about the issue. Accordingly, internal attributes and strategies of financial institutions may play a significant role in distinguishing its compliance with Islamic principles to respond to the society critiques about financial transactions.